EFISIENSI EKONOMI RELATIF USAHATANI JAGUNG ANGGOTA DAN NON ANGGOTA KELOMPOK TANI DI KABUPATEN LAMPUNG SELATAN - Muher Sukmayanto; Dyah Aring Hepiana Lestari; Adia Nugraha (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2019)
This study aims to analyze the profit of corn farming gained by members and nonmembers of farmer groups and relative economic efficiency of those members and non-members. This research was conducted in Natar District South Lampung Regency. The total of 76 farmers was used as samples including 36 members of corn farmer groups and 40 farmers nonmembers. It was analyzed through income analysis, and profit functions. The results showed that during farming seasons 1 and 2, the income of members of farmer groups was significantly higher than that of nonmembers. During farming seasons 1 and 2, members of farmer groups have a higher level of economic efficiency compared to nonmembers.Key words: corn farming income, farmer group members, relative economic efficiency